MEGALITIK DI SITUBONDO DAN PENGARUH HINDU DI JAWA TIMUR - Prasetyo, Bagyo (Berkala Arkeologi, 1999)
Based on the chronology of the development of megalithic culture in Situbondo, it can be seen that at least around the 5th century (according to carbon dating) there was even a long time before, that the megalithic tradition had taken root and continued to develop much later until the 15th century AD or maybe more after the collapse of the kingdom with Hinduism characteristics (Majapahit) in the East Java region. Megaliths as a tradition and the original belief of the Indonesian people do not seem to be easily shifted by external (foreign) religious influences. In general, the influence of foreign religions is only attached to the community within the palace or society that is included in the reach of the reins of government, while those outside are not affected by these elements. If you pay close attention, it seems that the people who support the megalithic tradition always build a fairly broad community.